Continuous‐time four‐quadrant modulator with inherent PVT cancellation. Issue 10 (1st May 2016) - Al‐Tamimi, K.; Thiyagarajan, P.; El‐Sankary, K.
Abstract : A continuous‐time four‐quadrant multiplier in subthreshold region is presented. Besides its simplicity, the structure features inherent process–voltage–temperature (PVT) variation cancellation while working under low voltage supply and dissipating an ultra‐low power. The PVT variation was alleviated through an inherent log/anti‐log cancellation technique, making it as a good candidate for bio‐potential acquisition systems. The input and output signals are currents resulting in a wider bandwidth and larger dynamic range compared with the voltage‐mode counterparts. The circuit is versatile and can be configured as a modulator, frequency doubler, and linear variable gain amplifier as shown in theory and simulation results.